The role of mind body interventions in the treatment of irritable bowel syndrome and fibromyalgia - Islam, Zarmina; D’Silva, Adrijana; Raman, Maitreyi; Nasser, Yasmin (Frontiers in Psychiatry, 2022)
Introduction Irritable bowel syndrome and fibromyalgia share similar pathophysiologic mechanisms including sensitization of peripheral and central pain pathways, autonomic dysfunction and are often co-diagnosed. Co-diagnosed patients experience increased symptom severity, mental health comorbidities, and decreased quality of life. The role of mind-body interventions, which have significant effects on central pain syndromes and autonomic dysregulation, have not been well-described in co-diagnosed patients. The aim of this state-of-the art narrative review is to explore the relationship between irritable bowel syndrome and fibromyalgia, and to evaluate the current evidence and mechanism of action of mind-body therapies in these two conditions. Methods The PubMed database was searched without date restrictions for articles published in English using the following keywords: fibromyalgia, irritable bowel syndrome, mind-body interventions, cognitive behavioral therapy, mindfulness based stress reduction, and yoga. Results Mind-body interventions resulted in improved patient-reported outcomes, and are effective for irritable bowel syndrome and fibromyalgia individually. Specifically, cognitive behavioral therapy and yoga trials showed decreased symptom severity, improved mental health, sleep and quality of life for both conditions individually, while yoga trials demonstrated similar benefits with improvements in both physical outcomes (gastrointestinal symptoms, pain/tenderness scores, insomnia, and physical functioning), mental health outcomes (anxiety, depression, gastrointestinal-specific anxiety, and catastrophizing), and quality of life, possibly due to alterations in autonomic activity. Conclusion Mind-body interventions especially CBT and yoga improve patient-reported outcomes in both irritable bowel syndrome and fibromyalgia individually. However, limited available data in co-diagnosed patients warrant high quality trials to better tailor programs to patient needs.